CHARACTERISTIC ANALYSIS OF LATERITE DEPOSIT AND BEDROCK IN MORONOPO AND WAILUKUM AREA, BULI REGION, EASTERN HALMAHERA DISTRICT, NORTH MOLUCCA PROVINCE - Rizki Ramadhan, Aditya
This research is prompted by the need to find new nickel resources in Moronopo and Wailukum area and the lack of detailed research about laterites and bedrock characteristics in both areas. The research area is part of PT. Antam UBPN North Maluku IUP. The coordinates of Moronopo's research area are 410.103-411.104mT and 82353-83386mU and Wailukum are at 412.369-413.763mT and 89.304-88.384mU 52N UTM zone, with Moronopo area of 0.94km2 and Wailukum area of 1.4km2. This research’s objective is to determine the characteristics of laterites and bedrock in Moronopo and Wailukum area. Data used in this research are DEM, LIDAR, field data and borehole data. Analysis on DEM, LIDAR and field data are used to determine geomorphological unit and topography in both areas. Analysis on field data are aimed to make geological map and crosssection in both areas. Geostatistic analysis on borehole data containing assay data and borehole description are ultilized to determine characteristic of laterites and bedrock in both areas. Buli region can be divided into 4 geomorphological units, Aluvial Plain Unit, Beach Plain Unit, Island Fault Block Unit, Ridge Fault Block Unit. The research area are located in Ridge Fault Block Unit. Based on petrography analysis, bedrock in Moronopo is moderately serpentinized harzburgite, and in Wailukum are serpentinite, moderately serpentinized orthopyroxene and weakly serpentinized olivine gabbronorite. Based on the kriging method on bedrock borehole sample, it is intrepeted that Moronopo Fault 1 & 2 could have increased sepentinisation intensity. Based on field observation, shear zone consist of a mixture various lithologies. Terniary SiO2-MgO-Fe2O3 diagram analysis shows that both areas are type of dry laterites with silica deposition. Laterites in Moronopo Area can be divided into red limonite, yellow limonite, soft saprolite and hard saprolite, and indicates good lateritization process. Based on topography, Moronopo Area can be divided into 3 area; hill slope 1, lowland basin and hill slope 2. Ore zone in hill slope 1 & 2 is caused by landslide and located in red limonite, yellow limonite, and uppert part of soft saprolite, and Ni has very strong – strong positive correlation with Co, Fe, MnO and Cr2O3. Good lateritization in lowland basin, makes Ore zone located in yellow limonite - soft saprolite and soft saprolite - hard saprolite bored, and Ni has medium positive correlation with Co, Fe, MnO and Cr2O3. Laterites in Wailukum Area can be divided into limonite and saprolite and indicates poor lateritization process. Ore zone only found in saprolite on laterite with serpentinite domination lithology, and Ni has strong positive correlation with Co, Fe, MnO and Cr2O3.